The consumption pattern and perception of using artificial sweeteners among the public in Tabuk region, Saudi Arabia - Alharthi, Sawsan A. S.; Alaisayi, Khulud Hassan A.; Alalawi, Lina Yousef S.; Alamri, Raniya Omar S.; Abu-Elfotuh, Karema; Alenazi, Tahani S.; Amirthalingam, Palanisamy; Albariqi, Hassan A. H.; Mohammed, Asmaa A.; Alsubayti, Norah; Hamdan, Ahmed M. E.; Kozman, Magy R. (Frontiers in Public Health, 2023)
Background Obesity and weight gain have become major problems worldwide. Thus, several forms of alternative intense sweeteners are extensively used, offering a non-caloric sweet taste. To the best of our knowledge, no research has studied either the consumption pattern or the perception of using artificial sweeteners in Saudi Arabia. Objectives Our research aimed to study the usage pattern of such artificial sweeteners in the Tabuk region and estimate the knowledge of and attitudes toward their usage among the population. Methods A cross-sectional study promoted on multiple social media platforms and face-to-face interviews in different malls and hospitals in the Tabuk region. We grouped the participants into two major groups: the users and the non-users of artificial sweeteners. Each group has been subdivided into a healthy subgroup and those with a medical record subgroup. Participants’ characteristics and their choice of sweeteners were analyzed using bivariate analysis. The age, gender, and education level of the participants were adjusted using binary logistic regression in order to adjust for potential confounders. Results A total of 2,760 participants were included in our study. We found that more than 59% of the participants that were over 45 years old were non-hospitalized non-hospitalized diseased irrespective of their usage of artificial sweeteners. Furthermore, females, graduates, diabetics were significantly high irrespective of their subgroup. Moreover, Steviana® is the most commonly used artificial sweetener. In addition, healthy participants showed a greater perception of the usage and adverse effects of artificial sweeteners. Furthermore, bivariate analysis using logistic regression revealed significant associations (p < 0.05) with confounders such as gender, age, and education level. Conclusion Educational programs and nutritional advice for the safe consumption and the daily permissible doses of artificial sweeteners are essential and should be directed specifically at females.